The unprotecting effects of employment protection: the impact of the 2001 labor reform in Peru - Miguel Jaramillo (Global Labor Organization (GLO), 2019)
According to the National Household Survey (ENAHO), approximately three out of four employment relationships within the formal sector of the Peruvian economy are based on temporary contracts. This percentage is larger than that of any OECD country and also considerably larger to that of any other country of the Latin American region. This study aims to elucidate the role that the 2001 labor reform played on these results and the effect this has had on variables associated to Peruvian workers' well-being. To this end, we exploit the information on contract type and start date (identified by the employment duration), which are reported on the household surveys, to analyze the decision between using fixed-term contracts or indefinite-term contracts. The average impact obtained from a differences-in-differences estimation with matching, having workers with contract but with no health insurance as a control group, is a reduction of 41 percent in the probability of having contracts of indefinite duration in the short term (up to five years after the reform), whereas the long-term impact has been a drop by 70 percent. These results are consistent, and similarly large, as those found in a model of simple differences controlling for workers' characteristics, firms and economic context. The results are robust to placebo tests and estimations by activity sectors and firm size. These results mean that, due to the reform, by 2015 over 900,000 jobs that could have been of indefinite-term were fixed-term contracts instead. Estimates based on Mincer equations suggest that this meant a loss of around 1.5 billion dollars in workers' labor income in 2015. Also, 36,000 workers would have affiliated to a union, had such reform not been implemented. These figures suggest than, instead of increasing workers' protection, the reform implemented by the Constitutional Court left a large portion of them unprotected.
Keywords: K31; J63; C52; 330; employment protection; labor reform; impact evaluation